A comparative perspective of knowledge management via social media: India and China. Issue 2 (2nd February 2015) - Liu, Michelle; Rao, Pramila
Abstract : Purpose: – This research paper aims to showcase current knowledge management (KM) practices via social media that is being adopted by organizations in India and China. India and China are considered leading economies in today's global market. Any understanding of management practices in these countries will help practitioners in doing businesses in these nations. Design/methodology/approach: – This conceptual paper analyzes KM practices in India and China using an in-depth analysis of the extant literature to provide a comparative perspective of KM policies in these two economies. This paper has used a wide range of scholarly and non-scholarly databases from ABI Global Inform to Business Source Complete to Google Scholar among others. Findings: – This research offers valuable insights into characteristic KM trends followed by Indian and Chinese firms. This paper also highlights different approaches adopted by these two cultures in managing their KM practices. The study also provides hypotheses that can be tested by potential scholars. This paper also offers theoretical models to understand this concept better. Practical implications: – This paper also provides implications for practice by identifying guidelines for global managers. These frameworks might serve as preliminary parameters for practitioners planning to establish KM practices in India and China. Originality/value: – This paper compares and contrasts KM practices in one of the two largest BRIC (Brazil, Russia, India and China) economies which have not been addressed in the literature before. It also combines two theoretical frameworks from different fields (information technology and human resource management) providing a richer viewpoint on the subject.